2021
DOI: 10.1038/s41593-021-00919-0
|View full text |Cite
|
Sign up to set email alerts
|

Precisely timed theta oscillations are selectively required during the encoding phase of memory

Abstract: Brain oscillations have been hypothesized to support cognitive function by coordinating spike timing within and across brain regions, yet it is often not known when timing is either critical for neural computations or an epiphenomenon. The entorhinal cortex and hippocampus are necessary for learning and memory and exhibit prominent theta oscillations (6–9 Hz), which are controlled by pacemaker cells in the medial septal area (MSA). Here we show that entorhinal and hippocampal neuronal activity patterns were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
(114 reference statements)
2
21
2
Order By: Relevance
“…By contrast, it is not clear why from the purely Hebbian learning framework that disrupting the theta cycle should impair that form of learning. Intriguingly, a recent report appears to be consistent with the predictions of our model: Quirk et al (2021) found that a highly selective disruption of the timing of the theta cycle produced selective deficits in learning. Even more selective tests of the specific temporal dynamics associated with the CA3 and CA1 could more specifically test our model.…”
Section: Novel Predictionssupporting
confidence: 91%
“…By contrast, it is not clear why from the purely Hebbian learning framework that disrupting the theta cycle should impair that form of learning. Intriguingly, a recent report appears to be consistent with the predictions of our model: Quirk et al (2021) found that a highly selective disruption of the timing of the theta cycle produced selective deficits in learning. Even more selective tests of the specific temporal dynamics associated with the CA3 and CA1 could more specifically test our model.…”
Section: Novel Predictionssupporting
confidence: 91%
“…PV interneurons in the hippocampus have previously been reported to be part of a microcircuit essential in regulating memory consolidation 64,65 , and our optogenetic manipulations could be associated with silencing of these cells to some extent. Moreover, although we did not observe changes in frequency bands other than theta, we cannot exclude that CA1 pyramidal neuron spike timing could be drastically altered when scrambling theta oscillations, while 8 Hz stimulation were shown to not result in increased hippocampal activity 17 , which could explain the differential effects of those stimulation patterns on working memory performance. The memory impairments we observed were likely non-cholinergic: firstly, in our immunohistological experiments we found virtually no expression of ChrimsonR in ChAT neurons of the MS. Secondly, our optogenetic stimulations were not associated with changes in hippocampal ripples, while previous reports indicate that ChAT neurons stimulation is associated with reduced ripple frequency 44,57 .…”
Section: Discussioncontrasting
confidence: 60%
“…While complete MS optogenetic inhibition has been associated with spatial memory impairments 13 , these effects could potentially be attributed to disruption of cholinergic functions 14,15 , which are known to be critical for memory function. The exact role of non-cholinergic MS PV cells in memory encoding and retrieval remains an active area of research and has only been described recently 16,17 . Since the MS provides the largest subcortical inputs to the hippocampus and is essential in generating and maintaining theta rhythms, disruption of MS activity is likely to impact downstream hippocampal physiology and working memory 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Microstimulation or optogenetic manipulations in animals hold the potential to modulate synchrony in a more spatially precise manner, testing the role of synchrony in maintaining specific representations. Indeed, rodent studies have reported selective modulation of synchrony by optogenetic methods ( Kidder et al, 2021 ; Quirk et al, 2021 ). Once we better understand the role of synchrony, the ability to selectively manipulate it could provide treatments for neural disorders ( Sreeraj et al, 2019 ).…”
Section: Manipulation Of Inter-areal Synchrony Alters Working Memory Performancementioning
confidence: 99%